Perencanaan dan Perancangan Mixed Use Building Terintegrasi Lingkungan di Kemayoran – Jakarta - Miarsono, Harry; Permana, Galih Andika; Mufrizon, Harry; Gea, Lepiter (Jurnal Pelita Teknologi, 2020)
Mixed Use Building Planning and Design of Environmental Integration in Kemayoran – Jakarta is a process of thinking about environmentally friendly and sustainable multifunctional building planning combined with the concept of building design integrated / connected with the environment or public facilities around the design location. Mixed used building planning in Kemayoran is one of the solutions to the problems facing the city of Jakarta as the capital of the State of Indonesia. Especially regarding the problem of population density, and limited land for the development of residential areas. The design of mixed use buildings is also intended to accommodate the need for a building / residential that is comfortable, integrated with the environment and public facilities so that it supports the lifestyle of the metropolitan city amid the limited land area of the city of Jakarta.